Association Between Gall Structural and Metabolic Complexity: Evidence from Pistacia palaestina - Daniela Batovska; Mirena Chakarova; Monica Dines; Ivayla Dincheva; Ilian Badjakov; Moshe Inbar (Plants)
Pistacia palaestina hosts several Fordini gall-forming aphid species, which manipulate its anatomy and metabolism, creating galls that provide nutrients and protection. This study compared the extended metabolic profiles of P. palaestina leaves and galls induced by Baizongia pistaciae, Paracletus cimiciformis, and Geoica spp. GC–MS analysis of ethyl acetate (EtOAc) and methanol (MeOH) extracts revealed a high abundance of shikimic acid and quinic acid isomers, along with diverse hydrocarbons, lipids, terpenoids, phenolics, and carbohydrates, each showing distinct distributions across gall types. Paracletus cimiciformis galls closely resembled intact leaves, exhibiting limited metabolic disruption. In contrast, the larger, more complex galls of Baizongia and Geoica underwent profound metabolic modifications. These aphids manipulate host metabolism, leading to triterpenoid and phenolics accumulation, which likely fortifies gall structure and enhances chemical defense. The considerable variation among individual trees suggests that specific host plant templates significantly influence the metabolic profile of the galls.